Successful management of cavernosal artery pseudoaneurysm using microcoil embolization - Masterson, John M.; Savio, Luis F.; Softness, Kenneth; Masterson, Thomas A.; Perez, Jesus Beltran; Bhatia, Shivank; Ramasamy, Ranjith (Translational Andrology and Urology; Vol 6, No 5 (October 26, 2017): Translational Andrology and Urology (Management of Penile Cancer), 2017)
Erectile dysfunction (ED) is a common condition among men and has several causes. Among men under the age of 40, pelvic or perineal trauma is the most common cause of ED. Pelvic or perineal trauma often results in arterial injury as the likely mechanism of ED. We present the case of a 14-year-old male diagnosed with a pseudoaneurysm causing arteriogenic ED secondary to blunt force trauma to the perineum. We successfully managed arteriogenic ED with superselective embolization using microcoils. We also conclude through a review of the literature that microcoil and Gelfoam yield similar outcomes. We believe that it is important for urologists to be familiar with the various treatment techniques used by interventional radiologists in order to properly manage post-traumatic arteriogenic ED.